Identifying Urban Agriculture Needs and Challenges for the Implementation of Green Labeling in Xochimilco, Mexico - Arroyo-Lambaer, Denise; Zambrano, Luis; Rivas, Miguel I.; Vázquez-Mendoza, Diana Laura; Figueroa, Fernanda; Puente-Uribe, Martha B.; Espinosa-García, Ana C.; Tapia-Palacios, Marco A.; Mazari-Hiriart, Marisa; Revollo-Fernández, Daniel; Jiménez-Serna, Alaíde; Covarrubias, Marco; et al. (Frontiers in Sustainable Cities, 2022)
The current global situation with a dominant economic development model producing social inequality, increment and intensification of urbanization has generated severe environmental degradation and an associated increase in the likelihood of pandemics. New strategies that strengthen sustainable food production are urgent in highly unequal countries as Mexico. In Mexico City, the most populated city of the country, a wetland system, named Xochimilco, still holds chinampas, a unique and ingenious food system dating from pre-Hispanic times. These days chinampas are the best example of urban sustainable agriculture production. Unfortunately, this system is under threat due to urbanization and industrial land-use changes. Among the strategies to promote sustainable modes of production and consumption is eco or green labeling, consisting of a voluntary environmental certification approach, and marketing and advertising tool, that can change producers' and consumers' behavior toward long-term sustainability. Although widely used, the benefits of green labels for producers are not always realized. This study aimed to learn more about the agro-ecological production process and commercialization challenges in Xochimilco and San Gregorio Atlapulco in Southern Mexico City to understand chinampa producers' needs and determine whether a green label can offer solutions in this vulnerable socio-ecological system, particularly suffering the effects of the COVID-19 pandemics. For this, a literature review and producers' mental model analysis based on network theory, were developed. Results show that non-resolved issues such as commercialization problems, consumers' unwillingness to pay a fair price, loss of healthy soil, and degraded water quality used for irrigation persist and can affect the benefits of a green label including to improve chinampa production and farmers' income. Farmers' current necessities comprised increasing profits, receiving financial advice to set prices of agro-ecological vegetables and production costs, among others. Under the current production and commercialization scenarios complying with the assessment cost of certification will be difficult for most producers; then, implementing the green label would probably fail to fulfill the benefits. Attending to former and persistent conflicts and satisfying chinampa producers' neglected necessities are essential before implementing any program.